NUMERALS IN LINGUISTIC AND CULTURAL CONTEXTS: STRUCTURE, FUNCTION, AND EVOLUTION (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This research explores the linguistic nature of numbers, emphasizing their structural and semantic roles in language. In both cultural and cognitive contexts, numbers are more than mere mathematical entities—they serve as symbols embedded in language and culture. Across all societies, numbers are central to everyday communication, appearing in speech, literature, and proverbs. The linguistic aspects of numbers have long attracted the interest of linguists, especially with their significance in cultural and spiritual practices. Numbers have deep-rooted meanings in various cultures, influencing how they are used symbolically in expressions, idioms, and proverbs [1].